Challenge Program on Water and Food: Volta Basin Development Challenge Management of Rainwater and Small Reservoir for multiple uses, 2012 Annual Reflection Report - CGIAR Challenge Program on Water and Food (CGIAR Challenge Program on Water and Food, 2012)
As a program designed for bridging research to development outcome, the CPWF considers regular reflection, learning and adaptive management as crucial elements in the implementation of the basin programs. Reflection implies that the project teams and key stakeholders take stock of what is going on in the project in terms of the science and the process and revisit basic assumptions that underpinned their research. Such reflection provides opportunities for the learning which directs adaptive management. In 2012, basin level reflection took the form of a Field Tour, Learning Events, and a Science Workshop, held between 29 June and 5 July.